Safety and efficacy of hydroxyapatite scaffold in the prevention of jaw osteonecrosis in vivo - de Almeida, Adriana Duarte; Leite, Fernanda Gomes; Chaud, Marco Vinícius; Rebelo, Márcia de Araújo; Borges, Liliane Cristine Ferreira de Souza; Viroel, Fabia Judice Marques; Hataka, Alessandre [UNESP]; Grotto, Denise (Wiley, 2018)
Two scaffolds of chitosan/sodium alginate/hydroxyapatite (Ch/NaAlg/Hap) 1:1:0.2 and 1:1:0.6 were evaluated in the prevention of bisphosphonate-induced jaw osteonecrosis. Two groups of rats (n = 24, according to the euthanasia time: 15 or 30 days after the last Zoledronic acid (ZA) administration) were subdivided in four subgroups (n = 6): I – Control (saline + teeth extraction); II – ZA 0.6 mg/kg + teeth extraction; III – ZA + teeth extraction + scaffold 1:1:0.2; IV – ZA + teeth extraction + scaffold 1:1:0.6. Jaws were evaluated histologically and blood was evaluated for hematological and biochemical parameters. Histopathology showed significant osteonecrosis in AZ group. The scaffold's implantation, despite the inflammatory process, were able to prevent the osteonecrosis. In the 15-day euthanasia group, an increase in red blood cells and platelets was observed in the subgroup II. Hemoglobin and hematocrit decreased in subgroup IV compared to II. Hepatic transaminases and creatinine concentration increased significantly in subgroup II. Calcium concentration increased in subgroup IV compared to II. In the 30-day euthanasia group, no differences among the groups were observed for any parameter. Scaffolds proved to be efficient and safe to liver and kidney function. Some hematological parameters were altered by the scaffold, but returned to normal concentrations over time. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1799–1808, 2018.
Keywords: bone regeneration; hydroxyapatite; osteonecrosis; scaffold; zoledronic acid